Factors Influencing the Decision to Use Sterilization Contraception Among Reproductive-Age Couples - Hardika, Mufida Dian; Sundari, Sundari (Knowledge Dynamics, 2025)
Background: Although permanent contraception is one of the most efficacious contraceptive methods, its adoption remains minimal in rural Indonesia, particularly in Madiun Regency. This situation underscores a paradox: demographic eligibility is present, yet adoption remains constrained, indicating underlying psychosocial obstacles. Prior research has infrequently examined the concurrent influence of motivation and attitude, resulting in a deficiency in comprehending the behavioural determinants of sterilisation choices. Methods: A cross-sectional quantitative study was performed with 138 couples of reproductive age in the jurisdiction of Bangunsari Health Centre. Data were gathered with a validated Likert-scale questionnaire that evaluated motivation and attitude. Statistical study encompassed chi-square tests and logistic regression to investigate correlations and identify primary factors. Results: The study revealed that 43% of participants shown little motivation, and 69% displayed negative attitudes towards permanent contraception. A substantial association was identified between motivation and attitude levels (p < 0.05), indicating that highly motivated individuals were markedly more inclined to possess positive attitudes. Principal obstacles comprised apprehension of irreversible adverse consequences, societal stigma, and insufficient spousal communication. Elevated motivation correlated with a sense of security, perceived efficacy of contraception, and fulfilment of intended family size. Conclusion: Motivation and attitude are critical behavioural factors influencing the decision to take permanent contraception. This study addresses a significant research gap by combining both dimensions within a specific rural context. To enhance adoption, family planning initiatives must include behaviour change communication (BCC), encourage partner-based counselling, and tackle emotional obstacles that prevent informed, voluntary contraceptive decisions.